(x+8)(9x+11)=0

Simple and best practice solution for (x+8)(9x+11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(9x+11)=0 equation:


Simplifying
(x + 8)(9x + 11) = 0

Reorder the terms:
(8 + x)(9x + 11) = 0

Reorder the terms:
(8 + x)(11 + 9x) = 0

Multiply (8 + x) * (11 + 9x)
(8(11 + 9x) + x(11 + 9x)) = 0
((11 * 8 + 9x * 8) + x(11 + 9x)) = 0
((88 + 72x) + x(11 + 9x)) = 0
(88 + 72x + (11 * x + 9x * x)) = 0
(88 + 72x + (11x + 9x2)) = 0

Combine like terms: 72x + 11x = 83x
(88 + 83x + 9x2) = 0

Solving
88 + 83x + 9x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(8 + x)(11 + 9x) = 0

Subproblem 1

Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8

Subproblem 2

Set the factor '(11 + 9x)' equal to zero and attempt to solve: Simplifying 11 + 9x = 0 Solving 11 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 9x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 9x = 0 + -11 9x = 0 + -11 Combine like terms: 0 + -11 = -11 9x = -11 Divide each side by '9'. x = -1.222222222 Simplifying x = -1.222222222

Solution

x = {-8, -1.222222222}

See similar equations:

| 16x^2-4x-20=0 | | x^2-1x+5=0 | | 4(x-1)-4=0 | | 2.4x+6.7=3.9x+25 | | -43+2y+3=2(3y-4)-4 | | 12x^2+11x+2=0 | | -6(5x+4)= | | 9x+17-8x=-6-12 | | 5y-5=16+10y | | 16x^2-16x-5=0 | | -4x+1+5x=-4+9 | | 8x^2=4-9x | | 8(c+5)= | | -25.5+0.1p=0.9p+5.3 | | -2-12=5x+16-4x | | 3=-gt^2+20t+16 | | 5x^2-5x-10=0 | | 4x+4=9x-30 | | 2=t+12 | | 4x^2+7xy-2y^2=0 | | y+3=-1+7 | | -4(3p+3)-28=2(2p+4) | | A(2)+2AB+B(2)=50 | | x-0.7=9.2 | | (x+9)(x-10)=-86 | | 1-1.6y=-6.2 | | 5x^2+xy=0 | | w^2-3w=4 | | 55=-16t^2+150t+70 | | 0.10x+.05(14-x)=.10(2) | | 7+2(4n+6)-n= | | 5x+4=-(x-16) |

Equations solver categories